Strategic Marketing Approaches to Enhance The Adoption of Toyota Battery Electric Vehicles in Indonesia, Tunas Toyota Cawang - Amalya Khalisha Nur El Islami; Harimukti Wandebori (Syntax Literate, 2025)
This research examines strategic marketing methods to enhance the adoption of Toyota Battery Electric Vehicles (BEVs) in Indonesia, concentrating on Tunas Toyota Cawang from 2022 to 2024. Despite the swift expansion of the Indonesian electric vehicle (EV) market, Toyota's battery electric vehicle (BEV) sales have been subpar, impeded by consumer misconceptions, insufficient charging infrastructure, formidable competition from economical Chinese brands, and a prevailing inclination towards hybrid vehicles. These challenges highlight the necessity for customized marketing methods to enhance Toyota's BEV footprint. The study used a mixed-methods approach, integrating quantitative data from consumer surveys and sales records with qualitative insights derived from interviews with stakeholders, customers, and competitors. This analysis investigates Toyota's segmentation, targeting, and positioning (STP) in East Jakarta, evaluates internal and external influences on BEV adoption, and delineates principal market constraints and possibilities. Findings indicate that insufficient understanding, range anxiety, and elevated initial prices hinder consumer adoption, notwithstanding governmental incentives and growing interest in sustainable transportation. Actionable recommendations are offered to boost awareness, improve customer engagement, and capitalize on market opportunities based on the findings. These encompass educational initiatives, partnerships with influencers, strategic pricing, and the enhancement of charging infrastructure. Toyota should distinguish its BEVs by highlighting reliability, sustainability, and cutting-edge technology. By tackling these obstacles with specific techniques, Toyota can enhance BEV adoption and fortify its competitive stance in Indonesia’s expanding EV market.